2014
DOI: 10.1093/bja/aet430
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory stroke volume variation assessed by oesophageal Doppler monitoring predicts fluid responsiveness during laparoscopy

Abstract: ΔrespSV and ΔrespPV predicted fluid responsiveness during laparoscopy under strict physiological conditions. FTc was not predictive of fluid responsiveness during laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
3
17
2
Order By: Relevance
“…Since laparoscopic procedures are more and more frequently performed and since severe intra-abdominal hypertension (such as abdominal compartment syndrome) reduces the reliability of PPV and SVV, Zlicar and colleagues [21] set out to investigate the influence of pneumoperitoneum on SVV’s and PPV’s predictive values, because of the moderately increased abdominal pressure. In the analysis of 56 patients, the authors found that SVV was a reasonably reliable fluid responsiveness predictor (AUC ROC : 0.80), but PPV less so (AUC ROC : 0.67), which was in accordance with the limited data published in the field [22, 23]. The optimal SVV threshold was 12.5% with a grey zone of 7.5–13%.…”
Section: Monitoring Of Fluid Responsivenesssupporting
confidence: 75%
“…Since laparoscopic procedures are more and more frequently performed and since severe intra-abdominal hypertension (such as abdominal compartment syndrome) reduces the reliability of PPV and SVV, Zlicar and colleagues [21] set out to investigate the influence of pneumoperitoneum on SVV’s and PPV’s predictive values, because of the moderately increased abdominal pressure. In the analysis of 56 patients, the authors found that SVV was a reasonably reliable fluid responsiveness predictor (AUC ROC : 0.80), but PPV less so (AUC ROC : 0.67), which was in accordance with the limited data published in the field [22, 23]. The optimal SVV threshold was 12.5% with a grey zone of 7.5–13%.…”
Section: Monitoring Of Fluid Responsivenesssupporting
confidence: 75%
“…Guinot et al found that SVV measured by esophageal Doppler was reliable and predicted fluid responsiveness with PP \ 15 mmHg with an area under the curve = 0.92 (95% CI 0.82 to 0.98) and no change in the threshold for fluid responsiveness. 73 Conversely, Hoiseth et al also found no difference in the threshold for fluid responsiveness with PP \ 15 mmHg but showed that both PPV and SVV were relatively poor at predicting fluid responsiveness. 74 Despite these conflicting results in practice, consideration should be given to the limitations of each dynamic index and the dynamic variables used in combination with changes in SV to ensure that fluid boluses are given at the appropriate time to improve hemodynamics without any increase in risk.…”
Section: Fluid Management In Laparoscopic Surgerymentioning
confidence: 96%
“…However, pneumoperitoneum and head‐down positions make goal‐directed fluid therapy indices difficult to interpret. Increased intra‐abdominal pressure decreases ventilatory compliance, which increases the ventilatory pressure required to deliver a given tidal volume , in turn increasing the variation in haemodynamic indices during volume‐controlled ventilation without the blood volume changing . For instance, Høiseth et al.…”
Section: Common Clinical Challengesmentioning
confidence: 99%